Methodological recommendations for teachers to form concepts related to the diamond vocabulary category in elementary school students. - Xakimova Zulayxo (Zien Journals, 2022)
This article provides methodological recommendations for primary school teachers on the formation of competencies related to rhyming words in students. There is also a special emphasis on the concept of competence in education
Keywords: competence; pedagogical competence; personal pronouns; adjectives